Does quality of early childhood education and care affect the home learning environment of children? - Susanne Kuger; Jan Marcus; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Both, a high quality of the Early Childhood Education and Care (ECEC) setting and a high quality of the home learning environment foster children's development. However, we know little about the interactions between ECEC quality and the home learning environment. We examine whether the child's attendance in a high ECEC quality setting improves the quality of her home learning environment. We use very rich data from the NICHD Study of Early Child Care and Youth Development (SECCYD), which provides detailed panel information through children's age of 6 months to 9 years on ECEC quality and on the child's home learning environment. Our analysis is based on a sample of 700 children who have been in non-family child care for at least 10 hours/week. We estimate level and value-added specifications and show that ECEC quality improves the home learning environment at various measurement points. The effects sizes indicate that an increase in ECEC quality by one standard deviation increases the home learning environment by about 0.08 standard deviations. Furthermore, results differ by sub-groups: The home learning environment from more advantaged children benefits more from higher ECEC quality. Thus the potential of high ECEC quality on the home learning environment is not effectively used for disadvantaged children. Policies could work on this potential link, in particular.
Keywords: J13; I20; I24; 330; ECEC quality; home learning environment; spill-over; disadvantaged children